Development of Petroleum E-Module Based on Guided Discovery Learning for Class XI Senior High School - Miftahul Jannah; Suryelita Suryelita (Universitas Negeri Padang, 2023)
Petroleum material studied at class XI senior high school. This material is considered by the teacher to be studied independently by giving reading assignments and exercises. The teaching materials used are a summary of the material and don’t contain images, videos, audio, or questions, and aren’t scientifically derived. Needed are teaching materials per the curriculum and technological advances, which are one through e-modules. This study aimed to develop a petroleum e-module based on gdl for class xi high school and determine its validity and practicality. The research type is design research with plomp’s model. This method consists of three stages of preliminary research, prototyping phase, and assessment phase. This study was limited to small groups at the prototype stage iii. The validity test was carried out by five validators. The practicality test was carried out by two chemistry teachers and twelve students. The data collection instruments were validity questionnaires and practicality questionnaires. The results of the validity questionnaire were analysed by the aiken’s v formula and the practical results using descriptive statistical formula. The results of the study show that the content validity of the e-module based on gdl- is valid (0.88), Then the construct validity was in the valid category (0.89). The practicality of teachers is in the practical category (79.86%), And students are in the very practical category (84.91%). Further research is needed, namely field tests to determine practicality and effectiveness on a broad scale.